Inhibition Index of Secondary Metabolite-Like Extracts of Bacillus Cereus Against Phytopathogenic Bacteria in Rice Cultivation - Mendoza, Yelitza Aguas; Cordero, Alexander Perez; Vergara, Donicer E. Montes (Journal of Posthumanism, 2024)
The presence of diseases in rice cultivation has become a limiting factor in rice yield and production. The bacterial panicle blast disease has generated large economic losses in the agricultural sector. One of the strategies commonly used by farmers to control the disease is the application of agrochemicals, but these can contaminate the environment and many microorganisms have acquired resistance. Endophytic bacteria are considered a tool to control pathogens through the production of secondary metabolites. The aim of this work was to evaluate in vitro the concentrated fraction of secondary metabolites produced by Bacillus cereus against Burkholderia glumae and Burkholderia plantarii which were characterized by gas chromatography coupled to mass spectrometry (GC-MS). The inhibitory effect against B. glumae and B. plantarii was observed by metabolite impregnation test on filter paper discs. The metabolites geraniol, geranate and sulcatone were identified and showed in vitro antagonism against the plant pathogens. The production of microbial secondary metabolites may be an alternative to replace agrochemicals in the future.